2013
DOI: 10.1152/jn.00990.2012
|View full text |Cite
|
Sign up to set email alerts
|

Cortical activity evoked by an acute painful tissue-damaging stimulus in healthy adult volunteers

Abstract: Everyday painful experiences are usually single events accompanied by tissue damage, and yet most experimental studies of cutaneous nociceptive processing in the brain use repeated laser, thermal, or electrical stimulations that do not damage the skin. In this study the nociceptive activity in the brain evoked by tissue-damaging skin lance was analyzed with electroencephalography (EEG) in 20 healthy adult volunteers (13 men and 7 women) aged 21–40 yr. Time-frequency analysis of the evoked activity revealed a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 58 publications
2
17
0
1
Order By: Relevance
“…In the studies conducted to date, the quantification of EEG ERPs has been completed with the highest degree of methodological consistency, complying with reporting standards for publication of ERP studies , and has consistently described a pain‐specific marker of central nervous system pain processing. While only one study has been published examining nociceptive ERPs evoked by a tissue damaging lance in adults, and the lance was applied to the palmar surface of the distal phalanx of the fifth finger as opposed to the lateral or medial aspect of the heel as in the infant studies, the findings of this study are consistent with the infant literature in that adults did demonstrate a distinct negative–positive ERP that presented at electrode site Cz approximately 100–300 ms after painful stimulus . The two studies that attempted to quantify infant emotional response to pain using left‐right EEG asymmetry found no evidence for reliable pain‐specific changes in EEG power or asymmetry indices, despite the detection of pain using behavioural measures .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In the studies conducted to date, the quantification of EEG ERPs has been completed with the highest degree of methodological consistency, complying with reporting standards for publication of ERP studies , and has consistently described a pain‐specific marker of central nervous system pain processing. While only one study has been published examining nociceptive ERPs evoked by a tissue damaging lance in adults, and the lance was applied to the palmar surface of the distal phalanx of the fifth finger as opposed to the lateral or medial aspect of the heel as in the infant studies, the findings of this study are consistent with the infant literature in that adults did demonstrate a distinct negative–positive ERP that presented at electrode site Cz approximately 100–300 ms after painful stimulus . The two studies that attempted to quantify infant emotional response to pain using left‐right EEG asymmetry found no evidence for reliable pain‐specific changes in EEG power or asymmetry indices, despite the detection of pain using behavioural measures .…”
Section: Discussionsupporting
confidence: 73%
“…Additionally, several of the studies appear to include the same infants across studies, which raises concerns related to potential selection bias as this was not reported. While the limited research utilising this method in adults have similar sample sizes , future research aiming to advance our understanding of optimal samples sizes to detect neurophysiological differences is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Electroencephalography, in contrast, is a non-invasive neurophysiological method that records the electrical activity of the brain at the scalp, largely from superficial regions, such as the somatosensory cortex, because voltage changes dissipate from deeper subcortical structures over a certain distance. It is possible to observe event-related changes in the EEG traces following certain stimuli, including noxious laser, pinprick and heel lance (Zhang et al 2012;Fabrizi et al 2013;Iannetti et al 2013). Recently, studies have identified an event-related potential in newborn infants and infants up to 1 year old, which is specific to noxious stimulation (Slater et al 2010b,c;Fabrizi et al 2011;Verriotis et al 2015).…”
Section: Infant Pain and The Cerebral Cortexmentioning
confidence: 99%
“…Extracellular field recording, including electroencephalogram (EEG), electrocorticogram (ECoG) and local field potentials (intracortical activity) are commonly used to monitor ongoing spontaneous brain activity and levels of anesthesia in human and rodent neonates but are also used to record specific potentials evoked by a sensory stimulus. Somatosensory potentials evoked by experimental noxious cutaneous stimulation [8][9][10][11] are commonly used to measure pain activity in the adult human and rodent brain 12 . Specific nociceptive potentials are also evoked by single, clinically required skin breaking procedures in the human infant brain 13,14 and have been used in this age group to measure the postnatal development of cortical pain processing 10 .…”
Section: Introductionmentioning
confidence: 99%